2015
DOI: 10.1080/15384101.2015.1004937
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal cell cycle: the neuron itself and its circumstances

Abstract: Neurons are usually regarded as postmitotic cells that undergo apoptosis in response to cell cycle reactivation. Nevertheless, recent evidence indicates the existence of a defined developmental program that induces DNA replication in specific populations of neurons, which remain in a tetraploid state for the rest of their adult life. Similarly, de novo neuronal tetraploidization has also been described in the adult brain as an early hallmark of neurodegeneration. The aim of this review is to integrate these re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
198
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(206 citation statements)
references
References 133 publications
7
198
0
1
Order By: Relevance
“…Intriguingly, apart from developmental and neoplastic diseases, cell cycle re-entry and DNA replication in neurons has been linked to neural degeneration and injury. Although terminally differentiated neurons are typically in a quiescent state having blocked their ability to Page 9 of 26 A c c e p t e d M a n u s c r i p t 9 proliferate, several regulators of G1 to S-phase transition are expressed in normal adult brain and could lead to cell cycle re-activation under specific circumstances such as neurotrophic factor deprivation, DNA damage and oxidative stress [92]. Neuronal cell cycle re-activation is normally followed by apoptosis even before signs of DNA synthesis in G1/S checkpoint [93][94] or after DNA replication [95].…”
Section: Page 6 Of 26mentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, apart from developmental and neoplastic diseases, cell cycle re-entry and DNA replication in neurons has been linked to neural degeneration and injury. Although terminally differentiated neurons are typically in a quiescent state having blocked their ability to Page 9 of 26 A c c e p t e d M a n u s c r i p t 9 proliferate, several regulators of G1 to S-phase transition are expressed in normal adult brain and could lead to cell cycle re-activation under specific circumstances such as neurotrophic factor deprivation, DNA damage and oxidative stress [92]. Neuronal cell cycle re-activation is normally followed by apoptosis even before signs of DNA synthesis in G1/S checkpoint [93][94] or after DNA replication [95].…”
Section: Page 6 Of 26mentioning
confidence: 99%
“…Neuronal cell cycle re-activation is normally followed by apoptosis even before signs of DNA synthesis in G1/S checkpoint [93][94] or after DNA replication [95]. However, increasing evidence suggest that postmitotic neurons can re-enter cell cycle, replicate their genome and survive with a twofold DNA content in several degenerative diseases (reviewed in [92] and [96]). Particularly, CDKand Cdc7-dependent MCM2 phosphorylation at Ser40/41 was observed in the cytoplasm of neurons from patients with Alzheimer disease, a strong indication of cell cycle re-entry and active DNA replication [97].…”
Section: Page 6 Of 26mentioning
confidence: 99%
“…1 in Electronic supplementary material). Moreover, the cell cycle arrest in G2-M is commonly found in neurodegenerative diseases such and PD, where some populations of neurons complete DNA synthesis and are able to pass through the S phase, but are arrested at the G2/M (Frade and Ovejero-Benito 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Mature neurons do not undergo cell proliferation and, if lost, are not replaced [24]. Recently, numerous studies have suggested that when the neurons are exposed into some conditions such as oxidative damage, target deprivation, DNA damage, they may reenter the cell cycle from G0 phase [25]. Moreover, once neurons re-entry the cell cycle, most of them always die.…”
Section: Discussionmentioning
confidence: 99%